"Cystic fibrotics could survive cholera, choleraics could survive cystic fibrosis"; hypothesis that explores new horizons in treatment of cystic fibrosis. Issue 6 (December 2015) - Azimi, Arsalan
Abstract: Cystic fibrosis, the most common inherited disease of white population, is a disease of CFTR channels, in which mucosal function of many organs especially respiratory tract is impaired. Decreased mucociliary clearance and accumulation of mucus in airways facilitates colonization of infectious microorganisms, followed by infection. Following chronic infection, persistent inflammation ensues, which results in airway remodeling and deterioration of mucociliary clearance and result in a vicious cycle. Here, it is hypothesized that cholera toxin (CT) could ameliorate symptoms of cystic fibrosis as CT could dilute the thickened mucus, improve mucociliary clearance and alleviate airway obstruction. CT strengthens immunity of airway mucosa and it could attenuates bacterial growth and reduce persistency of infection. CT also modulates cellular immune response and it could decrease airway inflammation, hinder airway remodeling and prevent respiratory deterioration. Thereby it is hypothesized that CT could target and ameliorate many of pathophysiologic steps of the disease and it explores new horizons in treatment of CF.